Ben Tilghman and the philosophy of art: in defense of the «last of the mohicans» - I. N. Nekhaeva (Омский научный вестник: Серия "Общество. История. Современность")
The article considers the view on the art of one of the most prominent figure of antiessentialism in modern art philosophy — Ben Tilghman. The radicality of his view lies in the denial of all art theories. According to Tilghman, the role of art theory is excessive and sometimes even harmful. When solving purely practical problems, art requires a practical approach rather than theoretical. Critical analysis of this view on the nature of art allows us to show the true source of its radicalism — the lack of linguistic feeling, which does not give Tilghman to strictly follow the language game accepted by him, while maintaining the continuity of his own reflections